2013
DOI: 10.1128/jvi.03183-12
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide Phylogenetic Relationship of Avian Poxviruses

Abstract: Poxvirus infections have been found in 230 species of wild and domestic birds worldwide in both terrestrial and marine environments. This ubiquity raises the question of how infection has been transmitted and globally dispersed. We present a comprehensive global phylogeny of 111 novel poxvirus isolates in addition to all available sequences from GenBank. Phylogenetic analysis of the Avipoxvirus genus has traditionally relied on one gene region (4b core protein). In this study we expanded the analyses to includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
149
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(165 citation statements)
references
References 42 publications
14
149
2
Order By: Relevance
“…This has been recently questioned by many authors [4][5][6]23] since some taxa like Columbidae and Accipitridae can be infected by a wide diversity of strains, however with different sensitivity depending on the virus involved. This apparent diversity could be explained by some infections occurring as accidental events, especially in zoological collections where many species are housed closely, and it is suggested that such an infection could not lead to sustainable epornitics [23]. However, in the present study, all genotypes identified were responsible for clinical infections in Houbara and lead to nodular lesions on legs, beaks or eyelids without any evidence of phenotype-genotype relationship.…”
Section: Discussionmentioning
confidence: 99%
“…This has been recently questioned by many authors [4][5][6]23] since some taxa like Columbidae and Accipitridae can be infected by a wide diversity of strains, however with different sensitivity depending on the virus involved. This apparent diversity could be explained by some infections occurring as accidental events, especially in zoological collections where many species are housed closely, and it is suggested that such an infection could not lead to sustainable epornitics [23]. However, in the present study, all genotypes identified were responsible for clinical infections in Houbara and lead to nodular lesions on legs, beaks or eyelids without any evidence of phenotype-genotype relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Avianpox reports are common in many countries and phylogenetic studies were described by Luschow et al (2004), Jarmin et al (2006), Manarolla et al (2010), and Gyuranecz et al (2013) with samples from the United States, Italy, Germany, and other countries. Molecular research correlated with clinical manifestations allow the identification and comparison of genetic strains by consulting a database of strains identified by infected species, country of origin, year of isolation, isolated type (cutaneous form, diphtheric, or mixed) and form of isolation (cultivation in embryonated eggs).…”
Section: Introductionmentioning
confidence: 99%
“…Avipox has been diagnosed in a broad range of avian species: from 278 species in 20 orders (van Riper & Forrester, 2007) using classical and molecular detection techniques (Bolte et al, 1999). Ten avipox viral species are recognized (Buller et al, 2012), although only three major avipox cladescanary poxvirus, fowl poxvirus, and psittacine poxvirus (Jarmin et al, 2006;Carulei et al, 2009)-and some minor clades (Gyuranecz et al, 2013) have been recovered by phylogenetic analysis. Several diagnostic techniques have been reported for avipox: histopathology was first reported in 1873, virus isolation was reported in the first half of the twentieth century and electron microscopy in the second half of the twentieth century (Bolte et al, 1999).…”
Section: Introductionmentioning
confidence: 99%